Red sea bream iridoviral diseases (RSIVD) - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2025)
Abstract: Red sea bream iridovirus (RSIV) is a virus in the genus Megalocystivirus, is considered an important cause of Red sea bream iridoviral diseases. This disease causes significant economic damage to marine fish farming in Asia. Several factors accelerate disease spread, including water temperatures of 20–25°C, peak viral shedding before or at death, and high susceptibility in fish under one year old. Symptoms found in infected fish are not specific, such as uncoordinated swimming, fins rotting, petechial hemorrhage at gills lamellae, skin ulcer concurrent with enlargement of spleen, kidney and liver. Indirect immunofluorescence (IIF) test and Polymerase Chain Reaction (PCR) were used for rapid diagnosis. For disease prevention, the administration of an inactivated RSIV vaccine using formalin-killed virus, in conjunction with biosecurity measures and best farm management practices, is a crucial strategy for mitigating the risk of viral outbreaks.